ANALYSIS OF FUEL COSTS INCURRED DURING TRANSPORTATION - Koropcsák, Vanessza Elizabet; Juhász, János (Advanced Logistic Systems - Theory and Practice, 2023)
The unexpected war situation in Europe caused extraordinary supply disruptions on the market of domestic and international raw materials. As a result, the companies found themselves in several unfavorable situations, which endangered their daily operations. The aim of the research work is how the fuel costs of companies performing transport tasks can be reduced, and to what extent they represent a financial burden - typically in the provision of daily activities. When purchasing a significant amount of fuel, the price difference provides an opportunity for development, which can be used to achieve significant annual cost savings. It can be beneficial for a business, as the cost saved can be booked or shown as profit. In this way, the development of processes within the company can come to the fore, as it can strengthen the weak points of the company. Keywords: raw materials, shipping, transportation, supply chain